Makna Hidup (Meaning in Life) pada Wanita yang Terdiagnosa Positif HIV di Masa Kehamilan - Ardhana, Dewa Ayu Venny; Abidin, Zainal; Hanami, Yuliana (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
The Human Immunodeficiency Virus (HIV) is a virus that targets the human immune system. Pregnancy accompanied by HIV carries the risk of transmission from the mother to the infant, both during gestation, during the birthing process, and through breastfeeding. Women infected with HIV during pregnancy undergo physical, psychological, and social changes. This study aimed to explore and understand the experiences and meanings attributed by participants to their lives after receiving a positive HIV diagnosis during pregnancy. The study employed a generic qualitative approach, analyzing data through inductive thematic analysis. Data collection was conducted through online semi-structured interviews with three participants meeting the following criteria: (1) women aged 26-33 years; (2) having experienced pregnancy and being diagnosed with HIV positive. The results of the study revealed five main themes that elucidate the processes and meanings of life for the participants, including 1) Frustration towards the "tragic event"; 2) "Coming Out" as an effort toward self-acceptance as people living with HIV; 3) Social support providing strength for people living with HIV; 4) Self-acceptance as a source of meaning in life; and 5) Living with HIV is an endless struggle.